Immunoglobulin phagocytosis by granulocytes from sera and synovial fluids in various rheumatoid and nonrheumatoid diseases. Issue 2 (April 1975) - Cats, A; Lafeber, G J; Klein, F
Abstract : (1) The phagocytosis of human IgG, IgM, and C3 by granulocytes from various rheumatoid and nonrheumatoid sera and synovial fluids (SF) was investigated by direct examination of the patient's leucocytes and indirect testing by incubation of normal donor leucocytes with various sera and SF. (2) In rheumatoid arthritis (RA) phagocytosis of IgM, IgG, and C3 was common from sera and SF. There was a strong correlation of IgM and C3 phagocytosis with the occurence of rheumatoid factor. The phagocytosed IgM is probably rheumatoid factor. In SF both the direct and indirect test method yielded equally positive results; in serum the direct test was negative throughout. (3) In systemic lupus erythematosus there was phagocytosis of IgG, IgM and C3 from serum (indirect test), IgM not being correlated with the latex-fixation test and probably of antinuclear antibody nature. Phagocytosis decreased after treatment of the disease. Sera from many other rheumatic disease frequently gave weak IgG phagocytosis, but rarely did IgM or C3. (4) IgG, and sometimes C3, was frequently taken up from IgG myeloma sera (indirect test). IgM and IgG were taken up from Waldenström's macroglobulinaemia sera, independent of IgM concentration. It is possible that an aggregation tendancy of particular paraproteins determines Ig uptake from these sera. (5) IgG was taken up from half of the studied sera of infectious diseases in the indirect test, including two cases with Hodgkin's disease as well. Three sera from patients with untreated trypanosomiasis were positive for IgG as well as for IgM. (6) Normal healthy control sera remained negative, even after prolonged preservation or frequent freezing and thawing: only among very old sera were a few positive observations recorded. Immunoglobulin phagocytosis appears to be a common phenomenon in a number of conditions. It seems probable that soluble immune complexes, or in other cases nonimmune aggregates, may cause phagocytosis.